Facial feature comparison between biological relatives - Teoh, Geraldine Shi En (2016)
Facial feature recognition techniques that allow fast and efficient face detection have gained popularity in recent years. Based on the concepts of Viola-Jones robust real-time face detection, this project aims to find facial features that are able to determine if two individuals are related.